FEATURES OF DIABETES MELLITUS DURING PREGNANCY - Ismoilov, Jamshid Abduraimovich; Egamberdiyeva , Yulduz Komiljon kizi; Mahmamuradova, Nargiza Negmatullayevna; Daminov , Abdurasul Takhirovich (Educational Research in Universal Sciences, 2024)
In modern conditions, pregnancy and childbirth in patients with diabetes mellitus pose a number of serious problems for endocrinologists and obstetricians. On the one hand, pregnancy complicates the course of the disease, complicating the normal intrauterine development of the fetus, which requires constant monitoring of the condition of the pregnant woman. On the other hand, diabetes mellitus is the cause of a variety of obstetric pathologies. According to WHO recommendations, the following types of diabetes mellitus in pregnant women are distinguished: 1) type I diabetes mellitus, diagnosed before pregnancy; 2) type II diabetes mellitus diagnosed before pregnancy; 3) gestational diabetes (this name includes any impaired glucose tolerance that occurs during pregnancy). The prevalence of all types of diabetes mellitus among pregnant women is 3-3.5%. The incidence of diabetes mellitus type I and II is 0.5-0.7%, diabetes in pregnant women - 1-3%. Perinatal mortality with a combination of diabetes mellitus and pregnancy is 3-5%, and in the absence of such a combination - 1-2%.